Postmodern doors into a modern community college: Of empires and entryways, of doors jammed open and door jambs broken - Cliff Falk (Adult Education Research Conference, 1994)
The sureness of the modern educational project has been undermined by shifting epistemological and material conditions. The shift from modernity to postmodernity develops its own incongruencies and anomalies as well as highlighting those extant during modernity. The author argues that the modern community college in British Columbia can be read postmodernly as a metaphor for and an exemplar of the modern American recolonization of the Canadian mind. Amelioration can result through developing a postcolonial, localized discourse.